Unusual association of NDM-1 with KPC-2 and armA among Brazilian Enterobacteriaceae isolates - Quiles,M.G. (2015)
We report the microbiological characterization of four New Delhi metallo-β-lactamase-1 (blaNDM-1)-producing Enterobacteriaceae isolated in Rio de Janeiro, Brazil. blaNDM-1 was located on a conjugative plasmid and was associated with Klebsiella pneumoniae carbapenemase-2 (blaKPC-2) or aminoglycoside-resistance methylase (armA), a 16S rRNA methylase not previously reported in Brazil, in two distinct strains of Enterobacter cloacae. Our results suggested that the introduction of blaNDM-1 in Brazil has been accompanied by rapid spread, since our isolates showed no genetic relationship.